Efektifitas Pengaturan dan Pengawasan Bisnis Financial Technology (Peer to Peer Lending) di Indonesia - Benuf, Kornelius; Agus Priyono, Ery; Mahmudah, Siti; Badriyah, Siti Malikhatun; Rahmanda, Bagus; Soemarmi, Amiek (Pandecta Research Law Journal, 2020)
In the industrial era 4.0 as it is now, the ease and speed of getting something are highly sought after, including the ease and speed of obtaining financial services. Financial Technology (Fintech) is a digital commercial service that offers and provides convenience and speed of financial services. The emergence of Fintech certainly makes it easy for people to get financial assistance. But as a state of law, Indonesia must regulate Fintech's business practices. Including the implementation of Fintech's business, it must be controlled and monitored by existing laws in Indonesia, not just stopping the formation of the rules, but also must be ensured that the rules apply effectively. This study aims to describe the basis for Fintech's business arrangements in Indonesia and will explain the effectiveness of the regulation in society. The writing method used is normative juridical, with a statutory approach, using secondary data by analyzing primary, secondary, and tertiary legal materials. Based on the research results, it is known that in Indonesia, Fintech's business is regulated by three institutions, namely the Ministry of Communication and Information, Bank Indonesia, and the Financial Services Authority. Regarding the effectiveness of the rules regarding the implementation of Fintech in Indonesia has not been going well because there are still shortages both in terms of legal structure, a legal substance, and legal culture.